Implementasi Peraturan Perundang-Undangan Tentang Diversi Tindak Pidana Anak di Polresta Yogyakarta - Eva Albatun Nabilah (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
processes to processes outside criminal justice. Diversion was only implemented in 2014, two years after the enactment of Law No. 11 of 2012 concerning the Child Criminal Justice System. The purpose of implementing diversion is to create restorative justice in the juvenile justice system. Restorative justice is believed to be able to overcome the high rate of child crime in Indonesia. In fact, in Yogyakarta, even though diversion has been implemented, the number of children committing crimes is still high. Based on this, the authors are interested in examining two things, namely examining the related implementation of diversion in Yogyakarta Police towards all criminal offenses that meet the requirements of attempted diversion and to see its implementation in terms of the objectives of the Child Criminal Justice System.This research uses a jurisdictional-empirical approach by looking at the suitability between the Law and the reality at the Yogyakarta Police. This research is descriptive analysis by conducting interviews and observations as data collection techniques.The results of this study, the authors conclude that not all child crimes in Yogyakarta Police are attempted diversion according to the mandate of the Child Criminal Justice System Act, even though the criminal offense of the child has fulfilled the requirements for diversion. This is because in practice, in addition to using diversion solutions, Yogyakarta Police also has another solution called "ADR". From the results of this study, the authors conclude that not all forms of restorative justice that are the objectives of the juvenile justice system are achieved. Of the 5 (five) points of the objectives of the juvenile justice system, three of them are achieved, namely: resolving child cases outside the judicial process; Avoid children from deprivation of independence; and Encourage the community to participate. While the other two, achieving peace between victims and children and instilling a sense of responsibility for children, has not been achieved.